Menuju Kurikulum Pendidikan Agama Islam Adaptif-Defensif bagi Muslim Minoritas - Huda, Saihul Atho Alaul; Hayaa, Ata Badrul; PS, Alaika M. Bagus Kurnia; Wafa, M. Aliyul (Universitas KH. A. Wahab Hasbullah, 2025)
This study examines the implementation of Islamic Religious Education (PAI) in Muslim minority areas, especially Denpasar, Bali, by highlighting adaptive and defensive dynamics in the curriculum. The results of the literature review show that the practice of PAI in public schools is still trapped in normative patterns, memorization, and is less connected to the social reality and local Islamic history. This condition creates a gap between the ideal achievement of the Independent Curriculum and the needs of the minority Muslim community. To answer these challenges, this study offers an adaptive–defensive curriculum model by combining four theoretical frameworks: the psychology of defense mechanisms, James A. Banks multicultural education, fiqh al-aqalliyyāt, and the SERVQUAL model for service quality evaluation. This conceptual model is expected to be able to strengthen Islamic identity, encourage social tolerance, and ensure educational justice. The study is conceptual and requires further validation through empirical research in the field.